OPIOIDS IN PAIN SYNDROME MANAGEMENT (part 1) - D. M. Arbuck; G. R. Abuzarova; G. S. Alekseeva (Вестник анестезиологии и реаниматологии, 2018)
The goal of this review is to inform doctors about new opioids currently used for routine medical practice in the most developed countries. This publication contains brief history, describes main mechanisms of opioid action, types and specific functioning of opioid receptors, it presents pharmacological parameters of the most frequently used opioids and their specific use in the clinical practice. In the light of increased interest towards pain management with opioids, the article will be useful for broad audience of doctors treating acute and chronic pain.